The Role of Skin Barrier in the Pathogenesis of Food Allergy - Neema Izadi; Minnelly Luu; Peck Y. Ong; Jonathan S. Tam (MDPI AG, 2015)
Food allergy is a serious public health problem with an increasing prevalence. Current management is limited to food avoidance and emergency treatment. Research into the pathogenesis of food allergy has helped to shape our understanding of how patients become sensitized to an allergen. Classically, food sensitization was thought to occur through the gastrointestinal tract, but alternative routes of sensitization are being explored, specifically through the skin. Damaged skin barrier may play a crucial role in the development of food sensitization. Better understanding of how patients initially become sensitized may help lead to the development of a safe and effective treatment for food allergies or better prevention strategies.